Traqueotomía percutánea y traqueotomía quirúrgica en UCI del Hospital de Especialidades Eugenio Espejo, Quito - Vélez, Jorge W (2018)
Background: tracheotomy is a procedure that is performed at the bedside of the critical patient and potentially shows complications. Currently, it is widely used for ventilatory management of patients in intensive care units, especially when prolonged periods of mechanical ventilation are required. Aim: to compare the results of surgical and percutaneous tracheotomy, during ventilatory management in the ICU. Material and methods: observational, prospective cohort study in 96 patients under mechanical ventilation in a multipurpose ICU, for which 2 groups were structured, the first managed with dilatational percutaneous tracheotomy and the other with open surgical tracheotomy, performed exclusively by the intensive care team of the unit, at the bedside, in a period of 15 months. Results: no significant statistical differences were observed between the two groups, in relation to complications of the technique, days of post tracheotomy mechanical ventilation and days of stay in the ICU, except for the time spent in its execution, with an average of 7.9 minutes for the percutaneous technique and 22 minutes for the surgical technique (p 0.003, 95% CI 1.33-15.8. Conclusions: the two techniques have similar incidence of complications, with respect to the time used is shorter for the percutaneous technique.